Legal Harmonization Between Aceh’s Qanun Jinayat and Indonesia’s National Criminal Code - Dimas Muhammad Yezar; Faisal Riza (Abdurrauf Law and Sharia, 2026)
The enactment of Law Number 1 of 2023 concerning the National Criminal Code introduces a new paradigm in Indonesia’s criminal justice system emphasizing proportionality, rehabilitation, restorative justice, legal certainty, and human rights protection. Within Indonesia’s plural legal system, the Aceh Qanun Jinayat functions as a special criminal law regime grounded in Islamic legal values and regional autonomy, regulating criminal acts through sanctions based on ta?z?r, moral education (ta’dib), deterrence, and social restoration (islah). However, differences between the Qanun Jinayat and the National Criminal Code in terms of sanction models, penal philosophy, legal objectives, and criminal measures raise significant issues concerning harmonization within the national legal system. This study employs a normative juridical method using statutory, conceptual, and comparative approaches to analyze the consistency, compatibility, and integration of legal norms concerning sanctions and criminal measures under the Aceh Qanun Jinayat and Law Number 1 of 2023. The findings reveal fundamental differences in the orientation of punishment, particularly regarding corporal punishment, imprisonment, and rehabilitation, while also identifying convergence in maintaining social order, justice, legal certainty, and human dignity. Harmonization may be achieved through proportional sanctions, restorative and rehabilitative approaches, clarification of legal subjects, and integration of maq??id al-syar?‘ah with constitutional and human rights principles to ensure legal certainty while preserving Aceh’s regional specificity [Pemberlakuan Undang-Undang Nomor 1 Tahun 2023 tentang KUHP Nasional memperkenalkan paradigma baru dalam sistem peradilan pidana Indonesia yang menekankan proporsionalitas, rehabilitasi, keadilan restoratif, kepastian hukum, dan perlindungan hak asasi manusia. Dalam sistem hukum pluralistik Indonesia, Qanun Jinayat Aceh berfungsi sebagai rezim hukum pidana khusus yang berlandaskan nilai-nilai hukum Islam dan otonomi daerah, mengatur tindakan kriminal melalui sanksi berdasarkan ta'zir, pendidikan moral (ta'dib), pencegahan, dan pemulihan sosial (islah). Namun, perbedaan antara Qanun Jinayat dan KUHP Nasional dalam hal model sanksi, filosofi pidana, tujuan hukum, dan tindakan pidana menimbulkan isu-isu penting terkait harmonisasi dalam sistem hukum nasional. Studi ini menggunakan metode yuridis normatif dengan pendekatan hukum, konseptual, dan komparatif untuk menganalisis konsistensi, kompatibilitas, dan integrasi norma hukum mengenai sanksi dan tindakan pidana berdasarkan Qanun Jinayat Aceh dan Undang-Undang Nomor 1 Tahun 2023. Temuan menunjukkan perbedaan mendasar dalam orientasi hukuman, khususnya mengenai hukuman fisik, pemenjaraan, dan rehabilitasi, sekaligus mengidentifikasi konvergensi dalam menjaga ketertiban sosial, keadilan, kepastian hukum, dan martabat manusia. Harmonisasi dapat dicapai melalui sanksi proporsional, pendekatan restoratif dan rehabilitatif, klarifikasi subjek hukum, dan integrasi maq??id al-syar?‘ah dengan prinsip-prinsip konstitusional dan hak asasi manusia untuk memastikan kepastian hukum sekaligus melestarikan kekhasan daerah Aceh.]